NITROGEN FERTILIZERS TECHNOLOGIES FOR COFFEE PLANTS - Chagas, Wantuir Filipe Teixeira; Guelfi, Douglas Ramos; Lacerda, Jordana Reis; Pinto, Leandro Campos; Andrade, André Baldansi; Faquin, Valdemar (Coffee Science - ISSN 1984-3909, 2019)
The application of urea in coffee crop has caused high losses of nitrogen (N) by volatilization, causing the low use and recovery of this nutrient. This low use of N may interfere in the growth and nutrition of the coffee crop and thus, influence the efficiency of the nitrogen fertilization. The aim of this work was to assess the growth, nutritional and physiological characteristics and the agronomic efficiency of the nitrogen fertilization with different nitrogen fertilizer technologies. The experiment was performed in a greenhouse in pots with a volume of 14 L. In each pot, it was performed the transplanting of two plants of coffee. The experimental design was entirely randomized, with four repetitions. The following nitrogen fertilizers were applied in the dose of 10g pot-1, splitted in three applications with interval of 50 days: Conventional urea; ammonium nitrate; urea + formaldehyde; Polyblen Extend®; Polyblen Montanha®; Urea + polyurethane; urea + plastic resin; ammonium sulfate + CaCO3 and the control, without N application. After cropping, it was evaluated the growth, nutritional and physiological parameters. Afterward, it was calculated two agronomic efficiency index of the nitrogen fertilization. The highest values of plants height, the total dry mass of plants and leaf area in coffee seedlings were found with the application of Polyblen Extend®. This blend also provided higher accumulation of N in the leaf and the whole plant. The application of Polyblen Extend® provided higher agronomic efficiency and also enhanced the photosynthetic rate in the coffee plants.